2022
DOI: 10.1002/ajh.26538
|View full text |Cite
|
Sign up to set email alerts
|

Mental health among patients with non‐Hodgkin lymphoma: A Danish nationwide study of psychotropic drug use in 8750 patients and 43 750 matched comparators

Abstract: Psychological distress following cancer diagnosis may lead to mental health complications including depression and anxiety. Non-Hodgkin lymphomas (NHLs) include indolent and aggressive subtypes for which treatment and prognosis differ widely.Incident use of psychotropic drugs (PDs-antidepressants, antipsychotics, and anxiolytics) and its correlation to lymphoma types can give insights into the psychological distress these patients endure. In this prospective matched cohort study, we used nationwide population-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…anxiolytics and antidepressants) prescriptions over 5 years compared to younger HL patients 35 . This difference was also observed for NHL patients >70 years 41 . While the previous findings may point to younger age being a significant risk factor for distress, it is possible that age may have differential effects depending on the type of distress examined.…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…anxiolytics and antidepressants) prescriptions over 5 years compared to younger HL patients 35 . This difference was also observed for NHL patients >70 years 41 . While the previous findings may point to younger age being a significant risk factor for distress, it is possible that age may have differential effects depending on the type of distress examined.…”
Section: Resultsmentioning
confidence: 69%
“…Twelve of sixteen studies suggest that age may be a significant factor, 25,27,31,32,34–41 although this association was not found to be significant in some studies 26,42–44 . For example, a cross‐sectional study by Smith and colleagues 32 found that younger age at study enrolment predicts worse mental health status, even when other sociodemographic/clinical characteristics and perceived impact of cancer were accounted for.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations